Wood Beam Damage Identification Based on the Curvature Mode and Wavelet Transform - Zhaobo Meng; Xiancai Ren; Shanqing Chai; Xin Wang; Tengfei Zhao; Feifei Gao; Shanwei Wang; Yufa Liu (Advances in Civil Engineering)
In the paper, a simple-supported wooden beam is used as the research object to identify the damage of the wood beam by finite element analysis and experimental research. First, ANSYS was used to establish the solid finite element model of the wood beam before and after the damage, and then the discrete wavelet transform was performed on the curvature mode of the wood beam before and after the damage, and the wavelet coefficient difference index was obtained after obtaining the high frequency wavelet coefficients. Then, the damage location of the wood beam was judged according to the sudden peak of the wavelet coefficient difference index, and the damage degree of the wood beam was estimated by fitting the relationship between the wavelet coefficient difference index and the degree of damage. Finally, the index was verified by the wooden beam test. The results show that the wavelet coefficient difference index can accurately identify the damaged location of the wood beams. The degree of damage to the wood beams at the damage location can be quantitatively estimated by fitting the relationship between the wavelet coefficient difference index and the degree of damage at the damage location. The research results provide a theoretical basis to identify wooden beam damage.